1993
DOI: 10.1148/radiology.187.2.8475270
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic metastases: interstitial laser photocoagulation with real-time US monitoring and dynamic CT evaluation of treatment.

Abstract: Fifty-five liver metastases in 21 patients were treated with interstitial laser photocoagulation (ILP). Tumors were irradiated with a neodymium yttrium aluminum garnet laser via optical fibers passed through 19-gauge needles inserted under ultrasound (US) guidance. Heating of the tumor was evident at real-time US as an expanding and coalescing echogenic zone around the needle tips. After ILP, dynamic computed tomography (CT) showed laser-induced necrosis as a new area of nonenhancement. Necrosis of tumor volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
119
0
12

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(135 citation statements)
references
References 0 publications
4
119
0
12
Order By: Relevance
“…In cases of recurrent tumors or those with ill-defined margins, alternative and multimodal oncological approaches are employed. The primary [40][41][42] and adjunctive [43][44][45][46] treatment of cancers by induced hyperthermia is a well established but burgeoning field of medical research. Here, temperatures in tumor-loaded tissues are elevated to 40-43°C [47] and above by selective or non-selective application of microwave, radio, ultrasound, alternating magnetic, infrared, or visible radiation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cases of recurrent tumors or those with ill-defined margins, alternative and multimodal oncological approaches are employed. The primary [40][41][42] and adjunctive [43][44][45][46] treatment of cancers by induced hyperthermia is a well established but burgeoning field of medical research. Here, temperatures in tumor-loaded tissues are elevated to 40-43°C [47] and above by selective or non-selective application of microwave, radio, ultrasound, alternating magnetic, infrared, or visible radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Under mild temperature increases, clinical studies indicate an acceleration in both perfusion and reoxygenation [50,51] of tumor tissues, thereby increasing the efficacy of cytostatic drug delivery (chemosensitization) and radiotherapy (radiosensitization), respectively. In all cases, clinical studies indicate statistically significant benefits to local tumor control and overall survival rates for primary [40][41][42] and conjunctive hyperthermia [52][53][54][55][56]. Although promising, conventional non-invasive hyperthermic strategies are often less selective than those basedon or used in combination with thermal contrast agents, in many cases, causing damage to surrounding healthy tissues, as well as significant discomfort.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with small cancers localized to the pancreas who are unfit for pancreatectomy because of their general medical condition and for whom there are no other therapeutic options, it would now seem justified to consider pilot clinical studies if the free flow of bile is protected by a biliary endoprosthesis. Laser fibres could be positioned in the tumour through needles placed percutaneously under ultrasound or computerized tomography (CT) guidance, as is done routinely in the management of small liver tumours (Amin et al, 1993), and the results assessed by contrast-enhanced CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…One of the advantages of local tissue destruction is that the trauma is small compared with surgery. It has been shown that interstitial laser thermotherapy induces well-defined and reproducible liver necrosis and that it may be efficient in local treatment of liver tumours (Amin et al, 1993;van Hillegersberg et al, 1994;Moller et al, 1996Moller et al, , 1997Tranberg et al, 1996).…”
mentioning
confidence: 99%